2016
DOI: 10.1016/s2095-3119(16)61358-8
|View full text |Cite
|
Sign up to set email alerts
|

Foliar application of sodium hydrosulfide (NaHS), a hydrogen sulfide (H2S) donor, can protect seedlings against heat stress in wheat (Triticum aestivum L.)

Abstract: Temperature extremes represent an important limiting factor to plant growth and productivity. Low concentration of hydrogen sulfide (H 2 S) has been proven to function in physiological responses to various stresses. The present study evaluated the effect of foliar application of wheat seedlings with a H 2 S donor, sodium hydrosulfide (NaHS), on the response to acute heat stress. The results showed that pretreatment with NaHS could promote heat tolerance of wheat seedlings in a dose-dependent manner. Again, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(27 citation statements)
references
References 67 publications
(77 reference statements)
1
26
0
Order By: Relevance
“…In order to evaluate the specificity and efficiency of WSP‐5 in the detection of H 2 S in Arabidopsis seedlings, additional controls using Arabidopsis wild‐type (WT) seedlings were carried out. Figure A–D shows a primary root of 10‐d‐old Arabidopsis seedlings incubated with increasing concentrations (0.0, 0.1, 0.5 and 2 mmol/L) of sodium hydrosulfide NaHS which is a recognized H 2 S donor molecule in animal and plant systems (Wang et al ; Aroca et al ; Yang et al ; Kharbech et al ; Zhang et al ; Muñoz‐Vargas et al ). Thus, an increase in the red fluorescence signal corresponding to the presence of H 2 S was also observed.…”
Section: Resultsmentioning
confidence: 99%
“…In order to evaluate the specificity and efficiency of WSP‐5 in the detection of H 2 S in Arabidopsis seedlings, additional controls using Arabidopsis wild‐type (WT) seedlings were carried out. Figure A–D shows a primary root of 10‐d‐old Arabidopsis seedlings incubated with increasing concentrations (0.0, 0.1, 0.5 and 2 mmol/L) of sodium hydrosulfide NaHS which is a recognized H 2 S donor molecule in animal and plant systems (Wang et al ; Aroca et al ; Yang et al ; Kharbech et al ; Zhang et al ; Muñoz‐Vargas et al ). Thus, an increase in the red fluorescence signal corresponding to the presence of H 2 S was also observed.…”
Section: Resultsmentioning
confidence: 99%
“…One of the major sources of ROS during times of abiotic stress is the photosynthetic apparatus. Documented effects of priming treatments with H 2 S donors [NaHS or sodium sulfide (Na 2 S)] include lowered accumulation of ROS and increased expression and activities of antioxidant systems (Fu et al , Yang et al ). In accordance with these observations, herein we observed that leaves from primed avocado plants accumulated lower H 2 O 2 after being exposed to frost and high‐light conditions.…”
Section: Discussionmentioning
confidence: 99%
“…These effects were attributed to the reduced accumulation of ROS and enhanced activities of antioxidant systems, but also possibly to inhibition of ethylene synthesis and/or signaling, modulation of sugar metabolism and control of autophagic processes (recent review by Ziogas et al ). Priming of plants with H 2 S donors (most commonly NaHS) has been shown to enhance their tolerance to a multitude of abiotic stresses including high light, drought, salinity, cold, heat, freezing, osmotic and heavy metal stress (Wang et al , Jin et al , Christou et al , Fu et al , Shi et al , Fan et al , Li et al , Yang et al , Du et al ).…”
Section: Introductionmentioning
confidence: 99%
“…The amplification of b-actin (Actin-F: 5 0 -CGAAGCGACATA-CAATTCCATC-3 0 and Actin-R: 5 0 -GAACCTCCACT-GAGAACAACAT-3 0 ) was used as an internal control (Yang et al 2016). Real-time PCR was performed with the following program: 95°C for 10 min, followed by 40 cycles of 95°C for 15 s and 60°C for 1 min.…”
Section: Methodsmentioning
confidence: 99%